Dampak Metode Debat terhadap Keterampilan Bahasa Arab (Berbicara) Siswa - Aziz Febriyanto, Rifqi; Manshur, Umar (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Arabic language learning demands strong speaking skills, a broad vocabulary, self-confidence, and critical thinking abilities. However, traditional teaching methods often fall short in effectively developing these aspects. One promising innovative approach is the implementation of debate methods in Arabic language instruction. This study aims to analyze the impact of implementing the debate method on students’ speaking skills, vocabulary acquisition, self-confidence, and critical thinking abilities at the Foreign Language Development Institute. This research employed a qualitative approach, utilizing observation, in-depth interviews, and documentation for data collection. Data analysis was conducted through data reduction, data presentation, and inductive conclusion drawing. The findings reveal that the debate method significantly enhances students' speaking skills, enriches their use of technical vocabulary, boosts their self-confidence in speaking Arabic, and sharpens their critical and analytical thinking skills. Nevertheless, some challenges were identified, such as difficulties in recalling newly acquired vocabulary. The debate method has proven to be an effective strategy for comprehensively improving students' Arabic language proficiency. This study contributes to the development of an active, debate-based learning model in Arabic language education and recommends further exploration of debate implementation on a broader and more longitudinal scale.